2021
DOI: 10.1002/mp.15330
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of gold nanoparticle photon radiosensitization from direct and indirect effects using a complete human genome single cell model based on Geant4

Abstract: To investigate the radiosensitization properties of gold nanoparticles (GNPs) and better understand the intricate deoxyribonucleic acid (DNA) damage induction mechanisms involved in GNP-aided radiotherapy, a single cell model with complete human genome based on the Geant4 Monte Carlo toolkit was applied. Materials and methods: A Geant4-DNA model was implemented to simulate direct and indirect DNA damage generated in the physical and chemical stages. In the physical stage, a mixed-physics approach was taken by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…For example, following Equation (), the number of 25 nm radius GNPs ( n GNP ) in a 5, 7.35 or 10 µm radius cell would be 1.96 × 10 4 , 5.27 × 10 4 , and 1.21 × 10 4 , respectively, to achieve a concentration of 20 mg/g. These numbers are consistent with the expected range for 50 nm diameter GNPs established by Zhao et al 8 . (see Figure 3 in that work).…”
Section: Methodssupporting
confidence: 93%
See 4 more Smart Citations
“…For example, following Equation (), the number of 25 nm radius GNPs ( n GNP ) in a 5, 7.35 or 10 µm radius cell would be 1.96 × 10 4 , 5.27 × 10 4 , and 1.21 × 10 4 , respectively, to achieve a concentration of 20 mg/g. These numbers are consistent with the expected range for 50 nm diameter GNPs established by Zhao et al 8 . (see Figure 3 in that work).…”
Section: Methodssupporting
confidence: 93%
“…31,32 It is also important to note that in vivo uptake to tumor (and other organs) can vary significantly from the injected GNP concentration. Zhao et al 8 established a range of approximately 10,000-50,000 GNPs per cell for 50 nm radius GNPs based on the in vitro works of Chithrani et al 33 and Peretz et al 34 ; this is consistent with our range of 10,540-63,240 GNPs per cell for the nominal cell size (Equation 1). Hainfeld et al 35 demonstrated tumor uptake of up to 15 mg/g after the injection of 11 nm GNPs at 4 g/kg mouse bodyweight.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations